Thermal-magnetic-elastic effect analysis of a thin current-carrying conical frustum shell - Bian, Y.H.; Zhang, C. (Прикладная механика, 2020)
A thermal-magnetic-elastic problem for a thin current-carrying conical frustum shell in a magnetic field is studied. The normal Cauchy form of nonlinear differential equations, which include in total eight basic unknown variables, are obtained by the variable replacement method. Using the Newmark’s stable finite equidifferent formulas and the quasi-linearization method, the nonlinear partial differential equations are reduced to a sequence of quasi-linear differential equations, which can be solved by the discrete-orthogonalization method. The temperature field in a thin conical frustum shell and the integral eigenvalues are derived after considering Joule’s heat effect in an electromagnetic field and the thermal equilibrium equation. The change of stresses, displacements, and temperatures in the thin current-carrying conical frustum shell with variation of the electromagnetic parameters is discussed. It is proved that the stresses, strains, and temperatures in thin shells can be controlled by changing the electromagnetic and mechanical parameters by considering a specific example. These results are expected to be a theoretical reference for further analysis of this case. Вивчено термомагнітопружну задачу для тонкої конічної зрізаної оболонки, що проводить струм і перебуває у магнітному полі. Отримано методом заміни змінних нелінійні диференціальні рівняння нормального за Коші типу, які включають всього вісім невідомих змінних. За допомогою стійких скінченних формул Ньюмарка і методу квазілінеаризації нелінійні диференціальні рівняння з частинними похідними зведені до послідовності квазілінійних диференціальних рівнянь, які далі можуть розв'язуватися методом дискретної ортогоналізації. З розгляду теплового ефекту Джоуля в електромагнітному полі і рівняння теплової рівноваги визначено температурне поле в тонкій конічній зрізаній оболонці і інтегральні власні значення. На спеціальному прикладі проаналізовано зміну напружень, зміщень та температури зі зміною електромагнітних параметрів. Отримані результати матимуть теоретичне продовження в дослідженні поставленої задачі